Overviewing Ecological Mindedness in Indonesian Education: From Regulation to Instructions - Yohanes Heri Pranoto (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Education, both as a product and a system, in Indonesia has openly disclosed up opportunities for the instillation of ecological values for students from primary, secondary, to higher levels of education. This distinctly becomes proof that the curriculum as a product of regulation is still open to forging, so ecological education commences and is delivered. This is the background of this article. To what extent is ecological education present in the education system in Indonesia? How are ecological values present in the learning process? This article raises those issues straightforwardly through the latest research references in the hope that it will serve as a content or summary of the process of seeding ecological values in the world of education that is worthy of being a reference for subsequent related studies. This article also presents some feasible recommendations, so ecological education can better "land" on the existing education system. In addition, the future of ecological education practices will also be elaborated in this article.